Reproducibility of Leak Point Pressure in Female Stress Urinary Incontinence - Hwang, Eu Chang; Kim, Sun Ouck; Kwon, Dong Deuk (Urology Journal, 2016)
Purpose: To assess the reproducibility of the Valsalva leak point pressure (VLPP) based on urodynamics in females with stress urinary incontinence (SUI). Materials and Methods: From October 2008 to December 2009, 65 consecutive women with urodynamically confirmed SUI underwent duplicate VLPP measurements. The intra-individual reproducibility of the VLPP recording obtained by one urologist was determined. The two observations were separated by a 10-min interval. Results: The differences between the repeated measurements were not significant (initial vs. repeat VLPP, 84.8 ± 19.9 vs. 86.7 ± 20.3 cmH2O; P = .094). Repeated VLPP measurements were reproducible. Defining intrinsic sphincter deficiency (ISD) as VLPP < 60 cmH2O, the diagnosis of ISD changed between successive tests in three cases (from 55 to 89, 58 to 64, and 61 to 55 cmH2O). Conclusion: In female SUI, the VLPP is a reproducible method for evaluating urethral resistance. For VLPP < 90 cmH2O, the diagnosis of ISD changed in repeated measurements in some patients; therefore, other clinical findings must be considered when deciding on a treatment method.